Deconjugating taurocholic acid with Bifidobacterium to mitigate obesity-driven cancer progression by restoring CD8+ T-cell infiltration - Ruoshui Yuan; Yuke Li; Yifei Wang; Qingxiang Li; Chuanbin Guo; Lin Wang (npj Biofilms and Microbiomes)
Abstract Obesity is linked to an increased cancer risk, and probiotics show promise in weight management. Here, we elucidate the precise mechanisms through which the probiotic Bifidobacterium breve (B. breve) modulates the immune response in obesity-associated tumours utilizing a Hepa1-6 cell-bearing hepatocellular carcinoma (HCC) model sensitive to high-fat diet (HFD)-induced obesity. HFD-induced obesity expedited HCC progression and fostered an immunosuppressive microenvironment. Treatment with B. breve enhanced cancer control by rescuing the local infiltration of antitumour immune cells. Elevated serum taurocholic acid (TCA) levels were negatively correlated with B. breve levels in obese HCC mice. TCA hindered the infiltration of CD8+ T cells into the tumour microenvironment and diminished their antitumour efficacy by blocking ERK phosphorylation. B. breve deconjugated TCA via its type 4 bile salt hydrolase (BSH), and this effect was diminished upon BSH inhibition by AAA-10. These results highlight the potential application of the probiotic B. breve in the multidisciplinary treatment of cancer in obese individuals.